Development of switching curcuit polarities of electromagnets DC - Aikeyeva, A.A.; Makhanov, K.M.; Tanskozhanova, A.R.; Rogovaya, K.S.; Nuradinuly, Zh.; Mukhtarova, P.A. (Publishing House of the KarSU named after E.A.Buketov, 2017)
This work is directed to the development of the management system of electromagnetic lifting installation. To develop such control system is necessary to create automatic system of switching the poles. The experiment model of levitation system is developed for carrying out prior experiments. The Arduino UNO platform on the basis of the Atmega328 microcontroller is chosen. In paper the description of L293D driver is presented and the principle of driver operation which is a part of the circit is considered.
Keywords: electromagnetic lifting installation; microcontroller; KT805 series transistor; L293D circuit driver